STUDI BIBLIKA SPRITUALITAS MANUSIA BARU BERDASARKAN SURAT EFESUS 4: 23-32 - Astuti, Tri (Shift Key : Jurnal Teologi dan Pelayanan, 2020)
The news of the New Testament can be summarized as; God wants us to be His children, in the image of His likeness. The problem is how can believer achieve the God's goal of becoming a new human being? In Ephesians 4: 23-32 Paul explains about how believer can have a true new human spirituality. The purpose of this research is to find out how believers can have true new human spirituality. The research method used is a qualitative biblical approach by using historical and grammatical analysis. The results found several important behaviors that need to be done by believers to experience the renewal of the quality of the spiritual mind, in order to grow into a new human being desired by God, that is, speaking according to the truth, controlling anger, working optimally and behaving affectionately.Â